Prospects and Legal Challenges Regarding Intellectual Property Rights in Metaverse Operations in Nigeria - Aidonojie, Paul Atagamen; Eregbuonye, Obieshi; Ibeh, Success; Antai, Godswill Owoche; Kolawale, Adesoji Adebayo (Wacana Hukum, 2024)
The Metaverse concept is regarded as a virtual reality where the lines between imagination and reality interact and blend with ease. However, the Metaverse concept tends to seem promising not just a digital revolution but an entire universe of immersive encounters. However, despite the relevance and potential, there are challenges and potential conflicts arising from integrating Metaverse technologies with the traditional legal frameworks governing intellectual property in Nigeria. Concerning this, the study examines the rising prominence of the Metaverse and the need for a comprehensive examination of its potential on intellectual property rights in Nigerian legal framework. The study adopts a hybrid method of study, and 348 questionnaires were sent to respondents residing in Nigeria. The results generated were analyzed using a descriptive and analytical method. Findings reveal the complicated connection between Metaverse technologies and established intellectual property norms. The study also elucidates other challenges, such as virtual property rights and the replication of real-world intellectual property in virtual environments, emphasizing the necessity for adaptive legal frameworks in Nigeria. The study therefore concludes and recommends there is a need for adaptive legal frameworks and formulation of specialized regulations for intellectual property within the Metaverse, and proactive measures to anticipate and address emerging challenges.